1995
DOI: 10.1002/ajmg.1320560202
|View full text |Cite
|
Sign up to set email alerts
|

Kabuki make‐up (Niikawa‐Kuroki) syndrome in the Byelorussian register of congenital malformations: Ten new observations

Abstract: We describe clinical manifestations and historical data on ten patients with Kabuki make-up syndrome. All patients are of European ancestry and all have the characteristics of the syndrome, including typical face, retarded physical development, and mild to moderate mental retardation. Two of the probands have low-normal intelligence. Prominent and broad philtrum was described as an important component manifestation of the syndrome. In three families some clinical manifestations of Kabuki make-up syndrome were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
9

Year Published

1997
1997
1999
1999

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 11 publications
(19 reference statements)
0
56
0
9
Order By: Relevance
“…Oliveira, personal communication]. Cleft lip/palate and hypodontia are main manifestations of VWS, but they are often present in KMS patients [Niikawa et al, 1988;Philip et al, 1992;SchranderStumpel et al, 1994;Ilyina et al, 1995;Burke and Jones, 1995]. Moreover, a patient with a 1q25-q32.1 deletion reported by Hamano et al [1987] had a facial appearance resembling those of KMS patients.…”
Section: Resultsmentioning
confidence: 99%
“…Oliveira, personal communication]. Cleft lip/palate and hypodontia are main manifestations of VWS, but they are often present in KMS patients [Niikawa et al, 1988;Philip et al, 1992;SchranderStumpel et al, 1994;Ilyina et al, 1995;Burke and Jones, 1995]. Moreover, a patient with a 1q25-q32.1 deletion reported by Hamano et al [1987] had a facial appearance resembling those of KMS patients.…”
Section: Resultsmentioning
confidence: 99%
“…Previously reported findings include horseshoe kidneys (3 in 70), double renal pelvis (3 in 58), duplication of the collecting system (3 in 16), hydronephrosis (3 in 70), renal hypoplasia (1 in 10), and megaloureter (2 in 58) [Niikawa et al, 1988;Philip et al, 1992;Ilyina et al, 1995]. Both of the patients described here had renal findings including case 1 with hydronephrosis and hydroureter and case 2 with a dysplastic kidney requiring transplantation.…”
Section: Discussionmentioning
confidence: 60%
“…Hydronephrosis has been reported in a few cases of KS [Niikawa et al, 1988;Philip et al, 1992], but renal dysplasia has only been reported once in the past and was not severe enough to require surgery [Ilyina et al, 1995]. To our knowledge no biliary or hepatic anomalies were reported previously.…”
Section: Introductionmentioning
confidence: 75%
“…A maioria dos casos é de ocorrência esporádica. A etiologia dessa síndrome é obscura, mas em algumas famílias há evidências sugerindo herança autossômica dominante 3,[6][7][8][9] . O primeiro caso dessa síndrome diagnosticado em paciente brasileiro foi relatado por Bever e Ende 10 .…”
Section: Discussionunclassified